Remembering the forgotten war : the enduring legacies of the U.S./Mexican War - Van Wagenen, Michael (Public history in historical perspective., 2012)
"This book answers the deeper question of how remembrance of the U.S.-Mexican War has shaped the complex relationship between these former enemies now turned friends. The distant violence becomes a new lens through which to view today's rivalries and resentments"--Page 7.